Towards A Competitive Advantage by Optimize Supply Chain Management (SCM) Processes - Li, Weidong; Li, Zhixiang; Liu, Shizhao; Zhao, Jiankun (Journal of Theory and Practice of Management Science, 2024)
Supply chains are the essence of any organization. They connect suppliers, manufacturers, and end customers in a network that is essential to create and deliver goods or services. Effective supply chain management (SCM) is the valuable way of consistent competitive advantage and improving organizational performance. Since competition is no longer between organizations, but among supply chains. The aim of this research is formulating the relationship between SCM processes (demand management, order fulfillment, manufacturing flow management, and product development and commercialization) and competitive advantage. Data collection was performed using Analytical Hierarchy Process (AHP). Research results show that there is asignificant relationship between SCM processes and competitive advantage, also conclude thatdemand management and order fulfillment are stronger indicators of competitive advantage than manufacturing flow management and product development and commercialization.